Thyroseq v3, Afirma GSC, and microRNA Panels Versus Previous Molecular Tests in the Preoperative Diagnosis of Indeterminate Thyroid Nodules: A Systematic Review and Meta-Analysis - Silaghi, Cristina Alina; Lozovanu, Vera; Georgescu, Carmen Emanuela; Georgescu, Raluca Diana; Susman, Sergiu; Năsui, Bogdana Adriana; Dobrean, Anca; Silaghi, Horatiu (Frontiers in Endocrinology, 2021)
Background: Molecular tests are being used increasingly as an auxiliary diagnostic tool so as to avoid a diagnostic surgery approach for cytologically indeterminate thyroid nodules (ITNs). Previous test versions, Thyroseq v2 and Afirma Gene Expression Classifier (GEC), have proven shortcomings in malignancy detection performance. Objective: This study aimed to evaluate the diagnostic performance of the established Thyroseq v3, Afirma Gene Sequencing Classifier (GSC), and microRNA-based assays versus prior iterations in ITNs, in light of “rule-in” and “rule-out” concepts. It further analyzed the impact of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) reclassification and Bethesda cytological subtypes on the performance of molecular tests. Methods: Pubmed, Scopus, and Web of Science were the databases used for the present research, a process that lasted until September 2020. A random-effects bivariate model was used to estimate the summary sensitivity, specificity, positive (PLR) and negative likelihood ratios (NLR), and area under the curve (AUC) for each panel. The conducted sensitivity analyses addressed different Bethesda categories and NIFTP thresholds. Results: A total of 40 eligible studies were included with 7831 ITNs from 7565 patients. Thyroseq v3 showed the best overall performance (AUC 0.95; 95% confidence interval: 0.93-0.97), followed by Afirma GSC (AUC 0.90; 0.87-0.92) and Thyroseq v2 (AUC 0.88; 0.85-0.90). In terms of “rule-out” abilities Thyroseq v3 (NLR 0.02; 95%CI: 0.0-2.69) surpassed Afirma GEC (NLR 0.18; 95%CI: 0.10-0.33). Thyroseq v2 (PLR 3.5; 95%CI: 2.2-5.5) and Thyroseq v3 (PLR 2.8; 95%CI: 1.2-6.3) achieved superior “rule-in” properties compared to Afirma GSC (PLR 1.9; 95%CI: 1.3-2.8). Evidence for Thyroseq v3 seems to have higher quality, notwithstanding the paucity of studies. Both Afirma GEC and Thyroseq v2 performance have been affected by NIFTP reclassification. ThyGenNEXT/ThyraMIR and RosettaGX show prominent preliminary results. Conclusion: The newly emerged tests, Thyroseq v3 and Afirma GSC, designed for a “rule-in” purpose, have been proved to outperform in abilities to rule out malignancy, thus surpassing previous tests no longer available, Thyroseq 2 and Afirma GEC. However, Thyroseq v2 still ranks as the best rule-in molecular test.